Exploring the feasibility of using very short answer questions (VSAQs) in team‐based learning (TBL). (24th March 2021) - Millar, Kate R.; Reid, Michael D.; Rajalingam, Preman; Canning, Claire A.; Halse, Omid; Low‐Beer, Naomi; Sam, Amir H.
Abstract: Background: Team‐based learning (TBL) currently relies on single best answer questions (SBAQs) to provide immediate feedback. Very short answer questions (VSAQs) are a reliable and discriminatory alternative that encourage learners to use more authentic clinical reasoning strategies compared to SBAQs. However, the challenge of marking VSAQs has limited their integration into TBL; we therefore explored the feasibility of VSAQs within a TBL session. Methods: An online platform was developed to allow immediate marking of VSAQs during the TBL sessions. As part of the readiness assurance process, students completed VSAQs and SBAQs, which were marked in real time. Results: Instructors were able to mark all VSAQs during the individual readiness assurance test (iRAT), which facilitated the provision of immediate feedback during the team readiness assurance test (tRAT). The mean time to mark five VSAQs was 422 seconds (SD 73 seconds). For VSAQs, the number of attempts to reach the correct answer ranged from 1 to 38, compared to 1 to 4 for SBAQs. In total, 71.6% of students agreed that using VSAQs in TBL helped to emphasise group discussions. Discussion: The wide range of attempts at, and students' perspectives of VSAQs are suggestive of their positive impact on student discussion during TBL. We demonstrate how new technology allows VSAQs to be feasibly integrated into TBL with the potential to enrich group discussions.